Corn and Soybeans in a Strip Intercropping System: Crop Growth Rates, Radiation Interception, and Grain Yield Components - Diego Verdelli; Horacio A. Acciaresi; Eduardo S. Leguizamón (International Journal of Agronomy)
Crop growth rates (CGR), radiation interception (IPAR), yields, and their components were determined in two crops monocultures (using one corn and two soybean genotypes) and in intercropped “strips,” during three growing seasons. Corn yield in the strips significantly increased in the three seasons (13–16%) as compared to that in the monocultures. This response was due to increased yield in corn plants of the border rows of the strips, which was highly correlated to an increased IPAR, allowing high CGR at critical crop stages. As a result, more dry matter was partitioned to grain and also an increased number of ears per plant were generated. Conversely, yields of soybeans in the strips were 2 to 11% lower than that in the monocultures, with variable significance depending on soybean cultivar and/or year. Grain number per unit area was the yield component most closely associated to yield variation in both crops. We believe that if yield components of this system are more closely identified, more appropriate genotypes will fit into strip intercropping, thus contributing to the spread of this technique and thus to the sustainability of actual massive monocultured agricultural systems.